MANAGERIAL OWNERSHIP MODERATES THE RELATIONSHIP BETWEEN ENVIRONMENTAL SOCIAL GOVERNANCE AND INVESTMENT OPPORTUNITY SET WITH PERFORMANCE - Khoirunnasikin; Holiawati; Ani Kusumaningsih (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the influence of Environmental Social Governance and Investment Opportunity Set on company performance, with managerial ownership as a moderation variable. The method used is quantitative, with secondary data obtained from the company's annual report. Of the total 172 companies registered, as many as 16 companies were selected as samples through purposive sampling techniques, so that data was obtained from 96 companies analyzed. The object of this study is a company that is a member of the BGK Foundation listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period. The results of the study show that Environmental Social Governance and Investment Opportunity Set have an effect on company performance. In addition, regression moderation testing showed that managerial ownership was able to moderate the relationship between Environmental Social Governance and financial performance. However, managerial ownership is not able to moderate the relationship between the Investment Opportunity Set and the company's performance. It is hoped that the results of this research can provide investors and academics with an understanding of the factors that affect the company's performance, as well as a reference for further research in the field of business and finance.